2023
DOI: 10.1001/jamanetworkopen.2022.52055
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Food Inadequacy and Cardiovascular Disease Risk in Black Individuals in the US From the Jackson Heart Study

Abstract: ImportanceFood insecurity disproportionately affects Black individuals in the US. Its association with coronary heart disease (CHD), heart failure (HF), and stroke is unclear.ObjectiveTo evaluate the associations of economic food insecurity and proximity with unhealthy food options with risk of incident CHD, HF, and stroke and the role of diet quality and stress.Design, Setting, and ParticipantsThis cohort study was a time-to-event analysis of 3024 Black adult participants in the Jackson Heart Study (JHS) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…How psychosocial-biologic pathways may converge to increase multimorbidity risk in PWH, especially for women and people in impoverished communities, is an area of active investigation. Social determinants of health and trauma history have been linked with chronic inflammation via activation of stress responses, which in turn affects comorbidity risk, potentially exacerbated in PWH and women . Among PWH, ongoing systemic inflammation and immune dysregulation despite ART is associated with NACM development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How psychosocial-biologic pathways may converge to increase multimorbidity risk in PWH, especially for women and people in impoverished communities, is an area of active investigation. Social determinants of health and trauma history have been linked with chronic inflammation via activation of stress responses, which in turn affects comorbidity risk, potentially exacerbated in PWH and women . Among PWH, ongoing systemic inflammation and immune dysregulation despite ART is associated with NACM development .…”
Section: Discussionmentioning
confidence: 99%
“…Social determinants of health and trauma history have been linked with chronic inflammation via activation of stress responses, which in turn affects comorbidity risk, potentially exacerbated in PWH and women. 35 , 36 , 37 Among PWH, ongoing systemic inflammation and immune dysregulation despite ART is associated with NACM development. 38 , 39 Women with HIV have higher levels of inflammation and immune activation than men with HIV, even after achieving HIV-1 suppression, which may contribute to sex differences in NACM.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of food insecurity for Black adults with cardiovascular disease was as high as 37.3% in 2013-2014, and the prevalence of food insecurity among Hispanic adults with cardiovascular disease was as high as 42.2% in 2017-2018 [24]. A prospective study showed that economic food insecurity was associated with significantly higher risk of coronary heart disease and systolic heart failure among 3,084 Black participants in the Jackson Heart Study, even after adjustment for baseline cardiovascular risk and socio-economic factors [27]. Hispanic/Latino adolescents are a particularly vulnerable group and have the highest prevalence of adolescent obesity in the United States [28].…”
Section: Ethnic Minoritiesmentioning
confidence: 99%
“…Some have hypothesized that FI decreases diet quality and thus leads to worse CVD outcomes. 8,20 Alternate hypotheses include the association of FI with impaired access to care [21][22][23] and increased stress and neurohumoral responses implicated in CVD.…”
Section: Introductionmentioning
confidence: 99%
“…8,20 Alternate hypotheses include the association of FI with impaired access to care 2123 and increased stress and neurohumoral responses implicated in CVD. 2426…”
Section: Introductionmentioning
confidence: 99%